The prognostic significance of serum interferon-gamma (IFN-γ) in hormonally dependent breast cancer - Todorovi?-Rakovi?, Nataša; Milovanovi?, Jelena; Greenman, John; Radulovic, Marko (Cytokine, 2022)
Background: Interferon-γ (IFN-γ) is a pleiotropic immunomodulatory cytokine. Because of its contradictory and even dualistic roles in malignancies, its potential as a biomarker remains to be unraveled. Aim: To evaluate the prognostic significance of serum IFN-γ in hormonally treated breast cancer patients. Material and methods: The study included 72 premenopausal breast cancer patients with known clinicopathological characteristics. All patients received adjuvant hormonal therapy based on hormone receptor-positivity. The median follow-up period was 93 months. IFN-γ serum protein levels were determined by quantitative ELISA. Prognostic performance was evaluated by the receiver operating characteristic (ROC), Cox proportional hazards regression and Kaplan-Meier analyses. Classification of patients into IFN-γlow and IFN-γhigh subgroups was performed by the use of the outcome-oriented cut-off point categorization approach. Results: The best prognostic performance was achieved by IFN-γ (AUC = 0.24 and p = 0.01 for distant events, AUC = 0.29 and p = 0.01 for local and distant events combined). Age and IFN-γ were prognostically significant in instances of all types of outcomes and IFN-γ was the independent prognostic parameter (Cox regression). There was a significant difference between IFN-γ values of patients without any events and those with distant metastases (Mann-Whitney test, p = 0.007). IFN-γ levels correlated significantly with nodal status and tumor stage (Spearman's rank order, r = −0.283 and r = −0.238, respectively). Distant recurrence incidence was 4% for the IFN-γhigh subgroup and 33% for the IFN-γlow subgroup (Kaplan–Meier analysis). Conclusions: Raised serum IFN-γ levels associate independently with favorable disease outcome in hormonally dependent breast cancer.
Keywords: Interferon gamma; Breast cancer; Hormonal therapy; Tamoxifen; Prognosis